Kiai, Media Siber, Otoritas Keagamaan: Aktivisme Dakwah Virtual Kiai Azaim di Era Pandemi Covid 19 - Nova Saha Fasadena (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2020)
Abstract: This study examines the preaching activities of Kiai on social media in the era of the Covid Pandemic 19. As is known, the presence of this pandemic has forced preachers from Islamic boarding schools to choose da'wah virtually. Kiai Ahmad Azaim, a caretaker of the Salafiyyah Islamic Boarding School Syafi'iyyah Ibrahimy Situbondo, East Java, is one of the Kiai who uses cyber media to carry out his preaching activities which were mostly carried out offline before the pandemic. This study argues that the virtual da'wah activism carried out by Kiai Azaim has implications for a shift in authority and at the same time the Kiai's popularity. Through the method of analyzing the assumptions of Kramer's religious authority, an interesting finding is obtained that in terms of opportunity, Kiai interprets cyber media as the right medium to reach wider congregations. In terms of strength, Kiai understands that the presence of cyber media will not affect the power of the pesantren media or traditional recitation. In terms of rights, Kiai considers that as long as the community continues to use them, their rights need to be fulfilled.